Alleviation of heavy metal stress and enhanced plant complex functional restoration in abandoned Pb–Zn mining areas by the nurse plant Coriaria nepalensis - Yuan, Xin-qi; Guo, Zhao-lai; Duan, Chang-qun; Yang, Jie; Tang, Hong; Li, Lin-yang; Li, Ting; Liu, Chang-e (Frontiers in Ecology and Evolution, 2022)
Heavy metal pollution caused by mining has been a topic of concern globally because it threatens ecological functions and human health. Nearly all current remediation strategies take into account only such short-term issues as how to reduce or stabilize the content of heavy metals in soil, how to reduce the toxicity of heavy metals, and how to preserve water, soil and nutrients. However, little attention is paid to such long-term issues as whether plants can survive, whether communities can be stabilized, and whether ecosystem functions can be restored. Therefore, improving plant diversity and community stability are key aspects of improved mine restoration. To explore the possibility of reconstructing plant complexes in mining areas, the local nurse plant Coriaria nepalensis was selected as the research object for a study in the Huize Pb–Zn mining area of southwest China. C. nepalensis could increase the contents of nutrient elements (C, N, and P), reduce the contents of heavy metals (Mn, Cu, Zn, Cd, and Pb), and strengthen the plant complex functions (diversity, functional traits, and complex biomass) in its root zone. In general, C. nepalensis can form fertility islands (survival islands) in mining areas, which facilitate the colonization and success of additional less stress-resistant species. We propose C. nepalensis as a key species for use in restoration based on its ability to restore ecosystem functions under extremely stressful conditions. We encourage combination of C. nepalensis with other nurse plants to reinforce the rehabilitation of ecosystem functions.